Modeling and simulation of traffic movements at semiactuated signalized intersections - Maria de Lurdes Simões (2010)
This work presents a microscopic stochastic simulation model that emulates the traffic movements at signalized intersections with semiactuated signal operation. This model uses the Awesim simulation language to implement and facilitate the evaluation of numerous operating scenarios associated with vehicle-actuated control strategies at isolated signalized intersections. A validation procedure was carried out, field data were collected, and delays and green times observed in the field were compared with those estimated by the simulation program. The adequacy of this model to represent real-world systems is shown. The structure of the model and the steps that were followed for its implementation are described. The relationship between simulated delays and the delays obtained from applying the Highway Capacity Manual model is analyzed. The impact of the maximum green time and the unit extension of green time assigned by the actuated system to each phase is also assessed. The model outputs include measures of effectiveness such as total vehicular delay, average green time, and average cycle length.